SUSTAINABLE COTTON CULTIVATION IN SALINE SOILS: CHALLENGES, INNOVATIONS, AND FUTURE PROSPECTS - BAIG, KS; ALI, Z; WARRAICH, IA; KHAN, SU; KAUSAR, R; KASHAF, A; GUL, N; KHAN, OU; NAWAZ, R; AHMAD, HT (Biological and Clinical Sciences Research Journal, 2023)
This review investigates the dynamic landscape of sustainable cotton cultivation in the challenging terrain of saline soils, exploring the intricate interplay of challenges, innovations, and prospects. Cotton, a vital global commodity, encounters significant impediments in regions where saline soils threaten agricultural productivity. The escalating salinity levels pose multifaceted challenges, impacting crop yield and fiber quality and triggering environmental degradation and economic instability in cotton-dependent regions. The examination of challenges encompasses the detrimental effects of salinity on cotton growth, the far-reaching economic implications, and the limitations of conventional farming practices in saline environments. Innovations, ranging from soil amendment techniques to developing resilient cotton varieties and integrating precision agriculture, emerge as transformative solutions to address these challenges. These innovations not only mitigate the immediate impact of salinity but also contribute to the overall sustainability of cotton farming. Emerging trends in sustainable cotton cultivation, policy considerations, and ongoing research initiatives present promising prospects. Agroecological approaches, advancements in remote sensing technologies, and government support stand out as key elements shaping the trajectory of sustainable cotton agriculture in saline soils. As we navigate this dynamic landscape, the review underscores the importance of a holistic and adaptive approach, offering insights for stakeholders ranging from farmers and policymakers to researchers and industry leaders invested in ensuring the resilience and sustainability of cotton cultivation in saline soils.